New dark ages - Kinsella, Warren, 1960- (Kinsella, Warren, 1960- X Gang series., 2018)
"It is a dangerous, divisive time in America. A far-right political candidate is seeking the presidency and stirring up hatred against minorities. The X Gang, meanwhile, have lost one of their friends to that presidential candidate - and are encountering manifestations of hate practically everywhere they go. With his band, the Hot Nasties, about to embark on its first North American tour, and several recent murders in the punk scene linked to its gigs, Kurt Blank and the rest of the X Gang have some difficult decisions to make. New Dark Ages is about surviving in a nasty, brutish, and short-sighted time - and whether one should just go along or fight back"--Back cover.